Impact of removing OPTN region from vascularized composite allograft allocation - Booker, Sarah E.; Howell, Jesse; Dolan, Thomas G.; Poff, Kelley; Laurie, Krissy; Cherikh, Wida S.; Klassen, David K.; Wainright, Jennifer L. (Frontiers in Transplantation, 2024)
On 6/18/2020, the Organ Procurement and Transplantation Network (OPTN) implemented new policy replacing OPTN region with a 500 nautical mile (NM) circle around the donor hospital for the purpose of vascularized composite allograft (VCA) allocation. We used OPTN data to assess deceased donor VCA transplants in the 3 years pre-(6/19/2017-6/17/2020) vs post-implementation (6/18/2020-6/17/2023). A total of 19 deceased donor VCA transplants were performed pre-policy (10 uterus, 3 bilateral upper limb, 1 unilateral upper limb, 3 face, 1 abdominal wall and 1 penis), and 11 post-policy (4 uterus, 1 bilateral upper limb, 2 face, 1 trachea, 2 abdominal wall, and 1 bilateral upper limb and face). Median distance from donor hospital to transplant hospital increased from 70 NM (range: 0-524 NM) pre-policy to 119 NM (range: 0-464 NM) post-policy. The majority of transplants in both policy eras were within 500 NM of the donor hospital (89.5% (N=17/19) vs 100% (N=11/11)) and most remained within the same OPTN region as the donor hospital (68.4% (N=13/19) vs 90.9% (N=10/11)). Although it is difficult to draw strong conclusions about the policy's impact due to the low transplant volume and timing of implementation relative to the COVID-19 pandemic, data in the 3 years post-implementation suggest that 500 NM circles were a reasonable replacement for OPTN region in VCA allocation. The OPTN will continue to review data to monitor the policy's impact and inform future changes to VCA allocation, such as the transition to continuous distribution, a points-based framework expected to replace the current framework.